Postpartum septic pelvic thrombophlebitis after caesarean delivery: a case report - Margarida da Silva Cunha; Ana Beatriz Godinho; Rosário Botelho; José Pinto de Almeida (Elsevier, 2018)
Septic pelvic thrombophlebitis is a rare puerperal complication. It is an important differential diagnosis of postpartum fever and abdominal pain and although the condition is well known its diagnosis can be challenging. We report a case of a 41-year-old woman with fever and right abdominal pain three days after an uncomplicated caesarean delivery. Clinical, laboratory and imaging exams were unremarkable and the patient was treated for endometritis. In the absence of improvement despite an antibiotic adjustment, a clinical diagnosis of septic pelvic thrombophlebitis was made, and the patient presented a good response to anticoagulation in conjunction with broad-spectrum antibiotic therapy. Keywords: Fever, Postpartum period, Abdominal pain, Caesarean section, Pelvic septic thrombophlebitis